Sistem Pakar Pengklasifikasi Stadium Kanker Serviks Berbasis Mobile Menggunakan Metode Decision Tree - Maryam Maryam; Huan Wendy Ariono (Jurnal Kajian Ilmiah, 2022)
World Cancer Observation states that in Indonesia cervical cancer ranks number two with a total of 9.2% of all cancer cases, cervical cancer which continues to increase in percentage every year due to the addition of new cases. It is important for the public to be aware of the symptoms that arise from cervical cancer. Lack of knowledge about cervical cancer from an early age increases the risk of death. This is because patients know cervical cancer when it is at an advanced stage. So it is important to know the symptoms of cervical cancer patients and their stage level in order to get the appropriate treatment. This research produces an expert system to help the public know the classification of cervical cancer stages. The system development method used is the decision tree method. The classification process uses 200 cervical cancer medical records with 12 symptoms. The decision tree method used has an accuracy value of 85.50%, recall 85.40%, and precision 86.74%. The expert system was developed using the flutter framework. The results of the study are in the form of an expert system mobile application that has been tested black box which is declared valid. This system can help the public know the results of the diagnosis of the symptoms experienced and the stage level accurately to apply the appropriate treatment.